0062 Race/ethnicity, Sleep Duration, and All-cause Mortality Risk in the United States. (25th May 2022) - Denney, Justin; Zamora-Kapoor, Anna; Hansen, Devon; Whitney, Paul
Abstract: Introduction: Health experts recommend that adults should sleep between 7 to 9 hours in a 24-hour period, with data indicating higher mortality risks both above and below these thresholds. However, no study to date has examined the association between sleep duration and mortality risk across racial/ethnic groups. Methods: Data from the linked mortality files of the 2004-2015 National Health Interview Survey (NHIS) were used to examine the association between sleep duration and all-cause mortality among U.S. adults. Of 278, 103 adults aged 25+, 22, 347 individuals died over the follow-up period. Sleep duration was coded as: <7 hours, 7 to 9 hours, and >9 hours. Race/ethnicity was categorized as: non-Hispanic (NH) White, NH Black, NH American Indian/Alaska Native, NH Asian, NH multiple races, and Hispanic. Cox Proportional Hazard models were used to estimate associations between sleep duration, race/ethnicity, and mortality. All results are reported as relative risk ratios (RRR). Results: Across the sample, we replicated previous research, finding increased mortality risk for those sleeping <7 hours or >9 hours in a 24-hour period. Relative to NH Whites, after adjustments for sociodemographic and socioeconomic variables, mortality risk for NH Blacks and NH multiracial individuals was statistically indistinguishable while NH Asians (RRR= 0.79; p <0.001) and Hispanics (RRR= 0.80; p<0.001) had lower risk. Interactions between sleep duration and race/ethnicity showed that NH White adults sleeping >9 hours experienced 1.82 times higher (p<0.001) risk than those sleeping 7 to 9 hours. This risk was greater than NH Blacks (RRR= 1.42; p<0.001), NH Asians (RRR= 1.00; p< .05), and Hispanics (RRR= 1.15; p <0.01). Further, stratified regression analyses showed heightened mortality risks only for NH Whites sleeping <7 hours (RRR= 1.06; p <0.05). Conclusion: The association between sleep duration and all-cause mortality risk varies by race/ethnicity. While sleeping <7 hours in a 24-hour period is thought to increase mortality risk, we found this is specific to NH Whites. Sleeping >9 hours is associated with a higher mortality risk, but more so for NH Whites than other groups. More research on sleep duration and mortality that takes race/ethnic specific risk factors into account is needed to identify causal mechanisms. Support (If Any): Health Equity Research Center (HERC) at Washington State University